(untitled) (Italian Journal of Public Health, 2010)
In modern societies, work is the source of most individual, corporate and community wealth. The level of each society’s health is therefore particularly vulnerable to disruption caused by employee illness. Today healthy workplaces are one of the most important determinants of health. However, public health has tended to completely ignore health in the workplace and occupational medicine has tended to ignore it in part. This article refers to the Italian and European context and, through a review of international recommendations, research and direct field experiences, presents workplace health promotion as an important tool in the field of public health. Through the years, several initiatives have been tested. One of the platforms that has demonstrated to be cost effective is based on the principles included in the Ottawa Charter which, when applied to the workplace, define workplace health promotion. In the last twelve years, the European Commission has recognized the workplace as a key determinant of health and has outlined a methodology of workplace health promotion as defined in the Luxemburg Declaration. The basis of this methodology is planning. Without correct strategy and policy development it will not be possible to create a sustainable society. The enforcement of Lisbon treaty seems to be a substantial step forward for Europe.